Relationship among the Expression of Lymphatic Vessel Density, Microvessel Density, Carcinoembryonic Antigenic mRNA, KAI1, and Kiss-1, and Prognosis in Patients with Non-small Cell Lung Cancer - Guowen WANG (Chinese Journal of Lung Cancer, 2012)
Background and objective In recent years, many studies have revealed the prognosis in patients with non-small cell lung cancer (NSCLC). In general, some clinic-pathological parameters have been related with prognosis. The aim of this study is to detect the relationship among lymphatic vessel density (LVD), microvessel density (MVD), expression of carcinoembryonic antigen (CEA) mRNA, metastasis suppressor genes (KAI1 and Kiss-1), and the prognosis of NSCLC patients. Methods Blood samples were collected from 57 cases of NSCLC. The transcription of CEA mRNA was detected via nested reverse transcriptase-polymerase chain reaction and micro-fluid chip. Immunohistochemistry was performed to detect the expression of LVD, MVD, KAI1 and Kiss-1 in the patients. All follow-up data were collected and analyzed. Results The overall five-year survival rate was 18%, and the median survival was 34 months. TNM stage, lymph node metastasis, and expression of MVD, LVD, CEA mRNA and Kiss-1 were factors to survival, as determined via single survival analysis. Multivariate analysis demonstrated that TNM stage, lymph node metastasis, and expression of CEA mRNA were independent prognostic factors for NSCLC patients. Conclusion The expression of MVD, LVD, Kiss-1 and CEA mRNA is related to the prognosis of NSCLC.